Optimasi Formulasi Tablet Lepas Lambat Ekstrak Seledri (Apium graveolens L.) Menggunakan Polimer Xanthan Gum dan Lubrikan Magnesium Stearat dengan Metode Simplex Lattice Design (SLD): Optimization of Celery Extract (Apium graveolens L.) Sustained Release Tablet Formulation Using Xanthan Gum Polymer and Magnesium Stearate Lubricant with Simplex Lattice Design (SLD) Method - Nur Azizah; Noval Noval; Putri Vidiasari Sudarsono (Jurnal Surya Medika (JSM), 2023)
Antihypertensive drugs undergo first-pass metabolism and therefore have low oral bioavailability. It causes an increase in the frequency of drug use and concentration fluctuations that affect patient comfort. The sustained release tablet formulation was chosen because it can deliver the active substance with good bioavailability. An active antihypertensive substance that can be used is celery extract because it contains flavonoids, so a sustained release tablet formulation was made using xanthan gum and magnesium stearate to produce a constant and controlled release rate. This study aims to knowing the results of celery extract sustained release tablet evaluation using different concentrations of xanthan gum and magnesium stearate, and also obtains the optimal formulation. The manufacture of tablets uses the direct compression method. Powder evaluations include flow property through a funnel, angle of repose, compressibility index, and moisture content. Tablet evaluations include organoleptic, weight uniformity, size uniformity, hardness, friability, disintegration time, and dissolution tests. The evaluation results data were analyzed using Simplex Lattice Design. The powder evaluation result of all formulations meets the requirements of flow property through a funnel, angle of repose, compressibility index, and moisture content. Physical evaluation of the tablets shows all formulations meet the requirement of weight uniformity, hardness, and friability tests. On the size uniformity test, all formulations do not meet the requirement. The disintegration time test results show that F1 does not meet the requirement. Meanwhile, the dissolution test results show that F4 is the best formula because it shows constant and controlled release rate. Based on analyzed using Simplex Lattice Design, the F4 is the most optimal formula with xanthan gum 52 mg and magnesium stearate 3 mg.